Morphofunctional state of the adrenal glands of rats subject to repeated exposure to magnesium chlorate - Islamov, Shavkat; Alikulov, Abdimumin; Shamatov, Islom; Makhmatmuradova, Nargiza; Kudratov, Rizo (BIO web of conferences, 2024)
With long-term administration of magnesium chlorate to animals at a dose of 1/20 LD 50 in the early stages (3-30 days), an increase in the functional activity of the adrenal cortex was established. At a later date (60-90 days), the development of atrophic and sclerotic changes was revealed. In the early stages of the study (days 3, 7), destructive and hemodynamic disturbances appear in the cortical substance of the organ. Subsequently, these changes increase, and on the 14th day, foci of necrosis form in the fascicular and reticular zones. On the 30th day, sclerosis of the capsule and the appearance of hydropic degeneration in the cells of the glomerular and fascicular zones develop. In subsequent periods (60 - 90 days), an increase in dystrophic and necrobiotic phenomena in all zones of the adrenal cortex and the appearance of atrophic changes were established. At the beginning of the study (days 3-30), a slight increase in the functional activity of the adrenal glands was determined. Initially, this occurs against the background of a decrease in the synthetic phase and an increase in the excretory phase of the secretory cycle of adrenocorticocytes. On the 14th day, a decrease in the excretion phase was detected in the zona glomerulosa. In the future (60–90 days), the activity of the adrenal glands is inhibited and their reserve capabilities are depleted. It is justified to maintain a low level of synthetic processes and reduce the release of hormonal products from glandular cells of all zones of the organ. In the medulla, as the period of drug administration increased, an increase in the number of N-cells was detected and by the end of the study there were more of them than A-cells. During the analysis, hemodynamic, destructive and necrotic phenomena were enhanced. Thus, at the beginning of the study, the secretory activity of chromaffin cells was moderate (days 3-30), increased on the 60th day and decreased to moderate values on the 90th day of the experiment.